Influences of pulsed electric field parameters on cell electroporation and electrofusion events: Comprehensive understanding by experiments and molecular dynamics simulations - Sujun Qu; Qiang Ke; Xinhao Li; Lin Yu; Shuheng Huang (PLoS ONE, 2025)
Electroporation and electrofusion are efficient methods, which have been widely used in different areas of biotechnology and medicine. Pulse strength and width, as an external condition, play an important role in the process of these methods. However, comparatively little work has been done to explore the effects of pulsed electric field parameters on electroporation and electrofusion. Herein, influences of pulse strength and width on the electroporation and electrofusion of phospholipid bilayers were systematically investigated by using experiments combined with molecular dynamics simulations. Experimental results and machine learning-based regression analysis showed that the number of pores is mainly determined by pulse strength, while the sizes of pores were enlarged by increasing the pulse widths. In addition, the formation of large-size pores is the most crucial factor that affects the fusion rate of myeloma cells. The same trend has taken place on coarse-grained and all-atom MD simulations. The result suggested that electroporation events occur only in an electric field exceeding the strength of threshold, and the unbalanced degree of electric potential between two membranes leads to pores formation during the process of electroporation. Generally, this work provides a comprehensive understanding of how pulse strength and width govern the poration event of bilayer lipid membranes, as well as guidance on the experimental design of electrofusion.